Spontaneous thrombosis in a post-traumatic Splenic pseudo-aneurysm. - Mohamad Saini, Suraini; Bux, Shaik Ismail (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Introduction: Splenic pseudo-aneurysm is an uncommon complication following splenic injury caused by blunt abdominal trauma. Pseudo-aneurysm is usually treated with splenic arterial embolisation. Spontaneous thrombosis of a splenic pseudo-aneurysm can occur but it is rare. Method: We report a case of spontaneous thrombosis in a post-traumatic splenic pseudo-aneurysm. The patient was managed conservatively as he was haemodynamically stable with a repeat CT scan on the 7th day showing a tubular enhancing structure in the upper pole of the spleen demonstrating the same attenuation value . Conclusion: This case illustrates a spontaneous resolution of splenic pseudo-aneurysm, which is a rare outcome of the condition.